Coupled elastodynamics of piston compression ring subject to sweep excitation. (September 2017) - Turnbull, R; Mohammadpour, M; Rahmani, R; Rahnejat, H; Offner, G
The piston compression ring's primary function is to seal the combustion chamber, thus mitigating gas leakage to the crankcase and avoiding loss of pressure loading. As a result, the ring is meant to conform closely to the cylinder surface which promotes increased friction. The compression ring is subjected to combustion pressure loading, ring tension, varying inertial force and friction. It is a slender ring of low mass, thus undergoes complex elastodynamic behaviour, when subjected to a multitude of forces. These motions occur in the ring's radial in-plane and axial out-of-plane dynamics, which comprise flutter, ring axial jump, compression-extension, ring twist and rotational drag. An implication of these motions can be loss of sealing, gas blow-by, loss of power and lubricant degradation/oil loss, to name but a few. Consequently, understanding and accurately predicting ring dynamic behaviour under transient conditions is an important step in any subsequent modelling for evaluation of cylinder system efficiency. There have been a plethora of investigations for ring dynamics, often decoupling the ring behaviour in its in-plane and out-of-plane motions. This approach disregards any transfer of dynamic energy from one degree of freedom to another which is only applicable to rectangular ring cross-sections. Alternatively, there are computationally intensive approaches such as finite element analysis which are not conducive for inclusion in any subsequent system level engine modelling where ring response alters in an instantaneous manner. This would require embedded finite element analysis within a transient analysis. This paper presents a finite difference numerical analysis for coupled in-plane and out-of-plane motions of compression rings with practical cross-sectional geometries, which are mostly not rectangular. The formulated method can be integrated into a system level transient cyclic analysis of ring-bore contact. The presented approach takes into account the energy transfer between different degrees of freedom. The predictions are validated against precise non-contact measurements of ring elastodynamic behaviour under amplitude-frequency sweeps. This approach has not hitherto been reported in literature and constitutes the main contribution of the paper.